Waterborne Vietnamese Australians and Sydney's Georges River parks and green spaces - Goodall, Heather (UTS ePRESS, 2011)
Waterborne: Vietnamese Australians and Sydney's Georges River parks and green spaces, has been created by talking with the Vietnamese Australians who live around the Georges River and who often visit its parklands. Here they explain their memories of their early homelands, which are given context with information about the histories of rivers and parks in Vietnam. The Vietnamese Australians highlighted talk about their hopes for parks in Australia and their actual experiences in the parks and rivers around their new homes near the Georges River.